Southeast Asia and the Middle East: Islam, Movement, and the Longue Durée - Fogg, Kevin W. (Studia Islamika, 2009)
Book Review : (Eric Tagliacozzo, ed. Stanford, CA: Stanford University Press, working with NUS Press in Singapore, 2009). Viii + 392 pages.This book has brought together scholars from around the world to begin to fill this gaping hole. Especially with regards to the influence of the Middle East on Southeast Asian (Muslim) society, the various articles add significantly to our understanding. The book also aspires to go beyond a limited, brief, local perspective by bringing together essays from over a millennium of inter-regional connections. The appendage of longue durée to the subtitle, invocative of the Annales school of structural history emerging out of France several decades ago, indicates a focus to broader trends and forces at work shaping the relationship. The immediate e?ect of this longue durée framework is seen, though, in the broad range of time periods addressed in the volume, beginning with the dawn of Islam and running through the present.DOI: 10.15408/sdi.v16i3.478